PERJANJIAN JUAL BELI KELAPA SAWIT ANTARA PETANI KELAPA SAWIT DENGAN TAUKE (PEDAGANG KELAPA SAWIT) DI KELURAHAN PADANG JOTO GADANG KECAMATAN PALEMBAYAN KABUPATEN AGAM PADA TAHUN 2014 - Hoga Retmi Hendri; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Approximately 70% of the people in the village of Padang Koto Gadang district of Palembayan, Agam regency hung their life with oil palm plantations and sell their produce to the tauke (palm oil traders). Selling harvesting by debt bondage system is indeed at first appeared that both parties acting in good faith, however, over time this transaction will result in losses for farmers because farmers usually sell the harvest below the production selling price. The problems discussed in this thesis is, First, how is the execution of a purchase agreement between the farmers and oil palm traders in Padang Koto Gadang, district of Palembayan, Agam regency 2014? Second, how is the legal protection of the oil palm farmers from debt bondage system which is done by the employer (palm oil traders) in Padang Koto Gadang district of Palembayan, Agam regency 2014? Third, how is the legal effort which is taken by the parties in the purchase agreemen in Padang Koto Gadang district of Palembayan, Agam regency 2014?The method of research in this study, using this type of research is sociological / empirical research sites jurisdiction of the High Court of Riau. In this research, data collection by interview, and literature study. After the data collected then analyzed qualitatively, then conclude with the deductive method is to analyze the problems of the general form into special shapes. From the results of this study concluded, the first, execution of a purchase agreement between the oil palm farmers in Padang Koto Gadang district of Palembayan, Agam regency 2014 is done with debt bondage system. This system makes the farmers suffered losses because of debts growing in the long term, the second, legal protection against oil palm farmers from debt bondage system in Padang Koto Gadang district of Palembayan, Agam regency 2014 is settled with the family principle with consensus, and present chairmen of indigenous families and communities in that area, the third, legal actions taken by the farmers have been regulated by Law No. 19 of 2013 on the Protection and Empowerment of Farmers in the form of the provision of facilities and infrastructure, provide insurance of land, providing education and counseling about the farmKeywords: Sale and purchase of palm oil, Debt bondage system, Village of Padang Koto Gadang